2019
DOI: 10.1080/16549716.2019.1621007
|View full text |Cite
|
Sign up to set email alerts
|

Is there a social justice variant of South–South health cooperation?: a scoping and critical literature review

Abstract: Background: In recent decades, global health scholars and policymakers have highlighted the burgeoning role of South-South cooperation (SSC) in health, claiming it constitutes a more just and even-handed approach to health cooperation. But the assertion that SSC inherently challenges power asymmetries and pursues egalitarian agendas and forms of interaction merits interrogation. Here we explore a transformative, counter-hegemonic, solidarity-oriented form of SSCsocial justice-oriented South-South cooperation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…A review by Birn and colleagues uncovered notable articulation of a set of values and strategies that characterize social justice oriented south-south cooperation compared to other types of health aid. The analysis was found to bear relevance for the conceptualization, policy development, and practice of equitable health cooperation, demonstrating that anti-hegemonic health solidarity is possible even amid considerable political constraints (Birn et al 2019). A recent review by Smith to identify factors affecting civil society influence in the pre-implementation stages of the policy process found that the power of civil society actors was enhanced when they joined strong epistemic networks and broader coalitions of stakeholders, were resourced, and framed issues in ways that resonated with national policies and political priorities (Smith 2019).…”
Section: Discussionmentioning
confidence: 97%
“…A review by Birn and colleagues uncovered notable articulation of a set of values and strategies that characterize social justice oriented south-south cooperation compared to other types of health aid. The analysis was found to bear relevance for the conceptualization, policy development, and practice of equitable health cooperation, demonstrating that anti-hegemonic health solidarity is possible even amid considerable political constraints (Birn et al 2019). A recent review by Smith to identify factors affecting civil society influence in the pre-implementation stages of the policy process found that the power of civil society actors was enhanced when they joined strong epistemic networks and broader coalitions of stakeholders, were resourced, and framed issues in ways that resonated with national policies and political priorities (Smith 2019).…”
Section: Discussionmentioning
confidence: 97%
“… 65 , 66 , 67 , 68 A feminist approach challenges interstate level politics by highlighting the relational power between individuals of different genders and races, and prioritising collaboration over coercion and human security over national security. 69 Neo-Marxist and heterodox international relations theory 70 anchors on political values around societal equity, counter-hegemony, and radical redistribution of resources. The concept of shadow diplomacy came from criticism of Western hegemony within the discipline of international relations, and suggests how international donors obscure structural power by subtly directing health initiatives, processes, and instruments.…”
Section: Global Health Diplomacy: International Relations Concepts An...mentioning
confidence: 99%
“…As a consequence of this new global order with new emerging actors, it is possible to acknowledge the growing importance of South-South cooperation in the current multilateral world that has driven a "genuine re-balancing in the international development architecture, development financing approaches and actors, and in shifting paradigms of aid, development and partnerships" (Power, 2011, p. 997), as well as in health assistance. Indeed, in recent years, we have been assisting in the burgeoning of South-South cooperation also in health (Birn et al, 2019), defined by the World Health Organization as "the exchange of expertise between actors (governments, organizations and individuals) in [low and middleincome countries-LMICs]. Through this model of cooperation, [these] countries help each other with knowledge, technical assistance, and/or investments" (World Health Organization, 2017).…”
Section: Introductionmentioning
confidence: 99%